THE TECHNOLOGICAL PRACTICES IN THE ADMINISTRATIVE FIELD AT A FEDERAL INSTITUTE - Martins Ribeiro, Alessandro; Martins Ribeiro, Adriano; dos Santos Pereira, Aliger (Revista Gênero e Interdisciplinaridade, 2021)
Introduction: The federal institutes (IFs) represent 27% of the technological education in the country, these entities that value teaching, research and extension are constantly undergoing innovations in the administrative sectors that increase the efficiency in providing service to the teaching, student and external communities. Methodology: The study aimed to report which technological practices inserted in the administrative sector of IF-Baiano, Teixeira de Freitas campus, during the Sars-Cov-2 pandemic, demonstrated efficiency in the administrative process. The project followed the precepts of the Research Ethics Committee Resolution (466/2012). Results and Discussion: The study obtained 90% of its effectiveness from 10 employees who make up the Department of Public Administration (DAP), among the inserted practices the meet rooms represented 4 (50%) of use during this period of the pandemic, the Unified System of Public Administration (SUAP) about 3 (30%) and VPN shared folder 2 (20%). The virtual rooms for meetings, along with communication platforms allow the continuity of telework, the use of SUAP helps in the processing of purchase processes, donation, waiver and hiring of servers, by sharing folders of sectors, within the sector servers is possible to allow the speed in processing invoices in the bidding or settlement. Conclusions: The use of technological resources through software enables the efficiency in the management of telework, especially in the current moment of the Covid-19 Pandemic, it collaborates to not interrupt the work and to accelerate especially the processing of administrative processes.